A population-based analysis of the global burden of epilepsy across all age groups (1990–2021): utilizing the Global Burden of Disease 2021 data - Yang, Ling-zhi; Guo, Yi; Wang, Zhi-qiang; Zhang, Chen-qi (Frontiers in Neurology, 2024)
ObjectiveTo investigate the trends in epilepsy prevalence, incidence, mortality, and disability-adjusted life-years (DALYs) in all ages, with risk factors for epilepsy - associated death, from 1990 to 2021.MethodsUsing the standardized Global Burden of Disease (GBD) methodologies, we evaluated the burden of epilepsy in 204 countries and regions from 1990 to 2021, aiming to derive a more precise representation of the health burden posed by epilepsy by considering four distinct types of epidemiological data, namely the prevalence, incidence, mortality, and DALYs. The presented data were meticulously estimated and displayed both as numerical counts and as age-standardized rates per 100,000 persons of the population. All estimates were calculated with 95% uncertainty intervals (UI).FindingIn 2021, there were 24,220,856 (95% UI: 18,476,943–30,677,995) patients with epilepsy, with an age-standardized prevalence rate (ASPR) of 307.38 per 100,000 persons (95% UI: 234.71–389.02) and an age-standardized incidence rate (ASIR) of 42.821 per 100,000 persons (95% UI: 31.24–53.72).The global age-standardized mortality rate (ASMR) of epilepsy was 1.74 per 100,000 population (95% UI: 1.46–1.92); The age-standardized DALYs rate (ASDR) were 177.85 per 100,000 population (95% UI: 137.66–225.90); 154.25 per 100,000 population for females [114.73–201.76], and 201.29 per 100,000 population for males [157.93–252.74]. All of the ASPR, ASIR, ASMR and ASDR of males were higher than those of females, and the ASIR of epilepsy was the highest in children aged 0–14, at 61.00(95% UI: 39.09–86.21), while the older adult group aged 70+ has the highest ASMR of 5.67(95% UI: 4.76–6.18). From 1990 to 2021, the number of epilepsy-related deaths and DALYs both decreased. However, the ASPR of epilepsy increased by about 6.9% (95% UI: −0.10–0.26), and the ASIR increased by almost 12% (95% UI: 0.05–0.33). The trends in ASPR, ASIR, ASMR and ASDR exhibited notable variations across different regions.ConclusionEpilepsy is an increasing global health challenge with rising prevalence and incidence. Results of this cross-sectional study suggest that despite the global decline in deaths and DALYs, Epilepsy remains an important cause of disability and death, especially in low SDI regions. An improved understanding of the epidemiology of epilepsy may potentially have considerable benefits in reducing the global burden of epilepsy, by aiding in policy-making in low-income countries, provide data support for research on epilepsy medications and treatment methods.